A mutational signature associated with alcohol consumption and prognostically significantly mutated driver genes in esophageal squamous cell carcinoma. (16th January 2018) - Li, X C; Wang, M Y; Yang, M; Dai, H J; Zhang, B F; Wang, W; Chu, X L; Wang, X; Zheng, H; Niu, R F; Zhang, W; Chen, K X
Abstract: Background: Esophageal squamous cell carcinoma (ESCC) is often diagnosed at an advanced and incurable stage. Information on driver genes and prognosticators in ESCC remains incomplete. The objective was to elucidate significantly mutated genes (SMGs), mutational signatures, and prognosticators in ESCC. Patients and methods: Three MutSig algorithms (i.e. MutSigCV, MutSigCL and MutSigFN) and '20/20+' ratio-metric were employed to identify SMGs. Nonnegative matrix factorization was used to decipher mutational signatures. Kaplan–Meier survival analysis, multivariate Cox and logistic regression models were applied to analyze association between mutational features and clinical parameters. Results: We identified 26 SMGs, including 8 novel ( NAV3, TENM3, PTCH1, TGFBR2, RIPK4, PBRM1, USP8 and BAP1 ) and 18 that have been previously reported. Three mutational signatures were identified to be prevalent in ESCC including clocklike C>T at CpG, APOBEC overactive C>T at TpCp[A/T], and a signature featured by T>C substitution. The T>C mutational signature was significantly correlated with alcohol consumption (OR: 3.59; 95% CI: 2.30–5.67; P < 0.001). This alcohol consumption signature was also observed in liver cancer and head and neck squamous cell carcinoma, and its mutational activity was substantially higher in samples with mutations in TP53 . Survival analysis revealed that TENM3 mutations (HR: 5.54; CI: 2.68–11.45; P < 0.001) and TP53 hotspot mutation p.R213* (HR: 3.37; CI: 1.73–8.06; P < 0.001) were significantly associated with shortened survival outcome. The association remained statistically significant after controlling for age, gender, TNM stage and tumor grade. Conclusions: We have uncovered several new SMGs in ESCC and defined an alcohol consumption related mutational signature. TENM3 mutations and the TP53 hotspot mutation p.R213* are independent prognosticators for poor survival in ESCC.